The winter people - McMahon, Jennifer (New York : Doubleday, 2014)
Coming of age in an old farmhouse, nineteen-year-old Ruthie begins a search for her agoraphobic mother and discovers the century-old diary of the farmhouse's long- ago resident, a grieving mother who died under mysterious circumstances.
Keywords: Women -- Fiction; Agoraphobia -- Patients -- Fiction; Diaries -- Fiction; Paranormal fiction; Horror fiction